De novo LAMP2 insertion mutation causes cardiac-only Danon disease: A case report - Wang, James Jiqi; Yu, Bo; Song, Xiuli; Wang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Danon disease is a rare disease caused by glycogen storage lysosomal disorder. It is related to the pathogenic mutation of the LAMP2 gene. In this case report, we present a patient with a novel pathogenic mutation (c.764_765insGA) with cardiac-only symptoms. Her family members do not carry the same mutation she does, suggesting this is a de novo mutation. Further tests revealed vacuoles and glycogen disposition in the patient's heart tissue and a significant decrease in LAMP2 protein expression. Protein structure remodeling of LAMP2 predicted that the mutant protein has conformational change lacking an important transmembrane domain, subsequently causing protein destabilization.